2016
DOI: 10.3892/ijo.2016.3550
|View full text |Cite
|
Sign up to set email alerts
|

Rifaximin, a non-absorbable antibiotic, inhibits the release of pro-angiogenic mediators in colon cancer cells through a pregnane X receptor-dependent pathway

Abstract: Abstract. Activation of intestinal human pregnane X receptor (PXR) has recently been proposed as a promising strategy for the chemoprevention of inflammation-induced colon cancer. The present study was aimed at evaluating the effect of rifaximin, a non-absorbable antibiotic, in inhibiting angiogenesis in a model of human colorectal epithelium and investigating the role of PXR in its mechanism of action. Caco-2 cells were treated with rifaximin (0.1, 1.0 and 10.0 µM) in the presence or absence of ketoconazole (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 27 publications
(26 reference statements)
1
14
0
Order By: Relevance
“…We detected that meclizine markedly inhibited phosphorylation of ERK and p38 triggered by RANKL. These results were in line with previous studies, suggesting that meclizine attenuates ERK phosphorylation in chondrocytes and rifaximin acts as a PXR agonist similar to meclizine significantly blocked p38 phosphorylation ( Matsushita et al, 2013 ; Esposito et al, 2016 ). Moreover, our data showed that meclizine obviously repressed RANKL-induced expression of NFATc1 and c-Fos, and subsequently inhibited the activation of osteoclast-derived marker genes, including cathepsin K and MMP9 , which can straightly degrade collagens in hard tissues ( Takayanagi, 2007b ).…”
Section: Discussionsupporting
confidence: 93%
“…We detected that meclizine markedly inhibited phosphorylation of ERK and p38 triggered by RANKL. These results were in line with previous studies, suggesting that meclizine attenuates ERK phosphorylation in chondrocytes and rifaximin acts as a PXR agonist similar to meclizine significantly blocked p38 phosphorylation ( Matsushita et al, 2013 ; Esposito et al, 2016 ). Moreover, our data showed that meclizine obviously repressed RANKL-induced expression of NFATc1 and c-Fos, and subsequently inhibited the activation of osteoclast-derived marker genes, including cathepsin K and MMP9 , which can straightly degrade collagens in hard tissues ( Takayanagi, 2007b ).…”
Section: Discussionsupporting
confidence: 93%
“…In Caco2 CRC cells, Rifaximin reduces PCNA protein levels and consequently decreases cell proliferation, also reducing mediators of cell migration and angiogenesis [69]. Rifaximin inhibits the activation of AKT, NF-κB, and p70S6K, leading to a reduction in HIF-1α levels and inhibition of the p38 MAPK signaling pathway [70]. Imperatorin, one of the major active coumarins found in the root of Imperata cylindrica Beauv with many pharmacological activities including anti-inflammatory, anti-coagulant, and anti-proliferative effects, was reported to greatly reduce HIF-1α levels by decreasing hypoxia in various types of tumors.…”
Section: Role Of the P38 Mapk Signaling Pathway In The Response To Otmentioning
confidence: 99%
“…This process works first by the release of VEGF, which then activates the Nuclear Factor Kappa B (NF-κB) pathway leading to an increase in nitric oxide synthase and thus nitric oxide. Nitric oxide then stimulates angiogenesis of new blood vessels needed by cancer cells to thrive [ 58 ]. Esposito et al (2016) found that PXR activation could inhibit this process via its inhibition of the NF-κB pathway leading to decreased levels of NO.…”
Section: Pxr and Breast Cancermentioning
confidence: 99%